Organización trófica de las mojarras (Pisces: Gerreidae) de la Ciénaga Grande de Santa Marta (Caribe Colombiano) - Arenas-Granados, Pedro (1992)
The feeding habits of the eight species of mojarras (Gerreidae) occurring at the Ciénaga Grande de Santa Marta are described. Three methods were used to analyze the food eaten by 365 specimens: gravimetric, frecuency of ocurrence and a relative importance indexo Mojarras are omnivorous and euriphagous fishes, eating a wide spectrum of items, mainly small invertebrates (bivalves, gastropods, ostracods, copepods, polychaetes) taken on the oyster banks located inside the Ciénaga and on the sand-muddy bottoms near the mouth of Ihe lagoon. Intraspecific competilÍon seems lo be lowered as a consequence of the spatial segregation of the populations and the diel variation of the food items. Percentage of replenished stomachs increases in Ihe high salinity periodo The usefulness of Ihe various food analysis methods is compared, and the frecuency of occurrence method is recommended for this group.